(untitled) (American Journal of Medical Science and Innovation, 2023)
In this article we report a case of ectopia cordis, which is a rare congenital malformation characterized by an extra-thoracic position of the heart. This is the thoracic-abdominal form, of antenatal discovery on a pregnancy of 35 weeks and 03 days, during an obstetric ultrasound monitoring pregnancy during the third trimester of pregnancy, made at the University Hospital Professor Zafisaona Gabriel, Mahajanga Madagascar. The objective of this work is to report the antenatal ultrasound diagnostic elements of this rare malformation. Ultrasound plays an important role in antenatal diagnosis and the search for other related malformations, especially in low-income countries.